Vegetation structure and livestock grazing intensity affect ground-foraging birds in xerophytic forests of Central-East Argentina - Dardanelli, Sebastian; Calamari, Noelia Cecilia; Canavelli, Sonia Beatriz; Barzan, Flavia Romina; Goijman, Andrea Paula; Lezana, Lucrecia (Elsevier, 2022)
Ground birds are strongly associated with the vegetation structure in natural environments under livestock grazing. Birds that fed on the ground may be the most affected by overgrazing, while those that fed on the shrub layer may respond positively to shrub encroachment in open xerophytic forest. Therefore, evaluating changes in bird species associated with a particular stratum can provide valuable information on the health, productivity, and functionality of the ecosystem. Here, we explore the relationships between vegetation structure and grazing intensity with the individual responses of terrestrial bird species in forests of Central-East Argentina. We tested the hypothesis that vegetation structure and grazing intensity affect the occupancy of 12 ground-foraging bird species. We used hierarchical single-species occupancy models with a Bayesian approach, considering points nested within farms, to estimate the influence of vegetation structure and grazing intensity on the bird occupancy. Vegetation structure variables were related to the occupancy of 11 out of 12 species. Three of these species also responded to grazing intensity. Occupancy of most open country bird species was favored by increasing grass cover but disfavored by increasing shrubs and tree density. Therefore overgrazing, with its consequent low grass cover, negatively affected the presence of open country bird species. On the other hand, occupancy of forest species was favored by either shrub or tree density or by forest age (larger diameter of trees at breast height - dbh). Based on specific responses of bird species, we propose that species directly related to grass cover and grazing intensity, such as the Spotted Nothura (Nothura maculosa), are potential indicator of low grazing intensity in forests of central-east Argentina. In turn, the Ultramarine Grosbeak (Cyanoloxia brissonii), a forest species associated with dense woody sites with high grazing intensity and low grass cover, could be a good indicator of overgrazing in these forests. Livestock management in these forests should promote environmental heterogeneity inside farms. Maintaining minimal livestock grazing in semi-open areas with mature trees and conserving areas of dense forest will be fundamental for achieving satisfactory compromises between the conservation of ground-foraging birds and livestock farming.